Fast Alkaline Hydrothermal Synthesis of Pyrophosphate BaCr2(P2O7)2 Nanoparticles and Their NIR Spectral Reflectance - Diego Emiliano Carrillo-Ramírez; Juan Carlos Rendón-Angeles; Zully Matamoros-Veloza; Jorge López-Cuevas; Isaías Juárez-Ramírez; Tadaharu Ueda (Nanomaterials, 2025)
Recently, the development of nanoparticle pigments has attracted interest in chemical preparation due to their potential functional properties, such as phosphate-based pigments. The present research focuses on the feasibility of synthesising the BaCr2(P2O7)2 pigment under hydrothermal conditions. The effect of the microstructural features of ceramic pigments (the crystalline structure, morphology, and particle size) on their optical properties (colour and reflectance) was also studied. The BaCr2(P2O7)2 compound was prepared in different fluid media, including water and NaOH solutions (0.5–1.0 M), at several reaction temperatures (170–240 °C) and intervals (6–48 h). The single-phase BaCr2(P2O7)2 did not crystallise without by-products (BaCr2O10, BaCr2(PO7)2) in water and the alkaline solutions, even at 240 °C for 48 h; in these fluids, the ionic Cr3+ species oxidised to Cr6+. In contrast, the BaCr2(P2O7)2 single-phase crystallisation was favoured by adding urea as a reductant agent (25.0–300.0 mmol). Monodispersed BaCr2(P2O7)2 fine particles with a mean size of 44.0 nm were synthesised at a low temperature of 170 °C for 6 h with 0.5 M NaOH solution in the presence of 50.0 mmol urea. The phosphate pigment particle grew to approximately 62.0 nm by increasing the treatment temperature to 240 °C. A secondary dissolution–recrystallisation achieved after 24 h triggered a change in the particle morphology coupled with the incrementation of the concentration of NaOH in the solution. The pyrophosphate BaCr2(P2O7)2 pigments prepared in this study belong to the green colour spectral space according to the CIELab coordinates measurement, and exhibit 67.5% high near-infrared (NIR) solar reflectance.